Disain Robot Pembersih Lantai untuk Pemerataan Beban Kerja Cleaning Service - Donny Montreano; Sigit Pradana (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2019)
Uneven workloads that occur in every process or every work station, impact on outcomes that are difficult to achieve and even fail. Or even if accomplished but by adding more effort, it creates new problems. This does not happen only in mechanical systems such as car engines or generators, but also occurs in human body systems. It can even impact psychological aspects that are difficult to measure such as jealousy among workers. This study consists of two topics that carry out simultaneously with the topic of workload and product design topics. The workload study, attempts to improve the uneven workload of cleaning service on the auditorium floor with the help of a self-sustaining floor cleaning tool. Begin by measuring the workload of cleaning service before this research implementation. Then ended with a measure again with staffing methodologies after research implementation. The product design topics attempts to reduce the amount of sensors which other previous research using 3 or 5 sensors to only 2 sensors that is LIDAR and Compass. This topics is using mechanum wheel straight on a NEMA 17 stepper as a simple drives system. The system can clean up to 252 m2 in 20 minute. It is expected that automatic floor cleaners can help smooth the workload of cleaning service so they don’t need to work very early long before office hour and no need to home long after office hour. Its expected to be applied to similar cases in other buildings.